SPE252 : Understanding sports competetive / Faculty of Sport Science and Recreation - UiTM, Faculty of Sport Science and Recreation (Fakulti Pengurusan Maklumat, UiTM Kampus Puncak Perdana, 2023)
The course is designed to introduce students to basic concepts of competitive sports programmes. The contents of the subject of this subject would include the various categories of sports activities which includes indoor games, field games, individual and team events and highly specialized such as archery, shooting and golf. It would also include management process that should be applied into the organization of these sports.